A new species of predaceous midge in the genus Stilobezzia Kieffer from Mexico (Diptera: Ceratopogonidae) - Huerta, Heron; Grogan, William L. Jr (Zootaxa, 2021)
The predaceous midges (Diptera: Ceratopogonidae; tribe Ceratopogonini) in the genera Schizonyxhelea Clastrier & Stilobezzia Kieffer in Mexico were recently addressed by Huerta & Grogan (2017) who described one new species in each of these genera. A re-examination of specimens in the Colección de Artrópodos con Importancia Medica (CAIM), from the states of Morelos and Yucatan, revealed an undescribed species that was previously identified as Stilobezzia (Stilobezzia) femoralis Lane & Forattini from Yucatan by Huerta (2002) and Huerta & Grogan (2017). Herein, we describe and illustrate this species from the states of Morelos & Yucatan, Mexico, as Stilobezzia (Stilobezzia) tobiasi Huerta & Grogan n. sp.